MANGO GINGER SUPPLEMENTATION MAY PROTECT BONE DAMAGE INDUCED BY METHOTREXATE IN RATS - Erten, Fusun; Tuzcu, Mehmet; Orhan, Cemal; Ozercan, Ibrahim Hanifi; Balci, Tansel Ansal; Tuzcu, Zeynep; Şahin, Kazım (Polskie Towarzystwo Farmaceutyczne, 2019)
Mango ginger (MG) has anti-inflammatory and antioxidant properties. The objective of this study was to investigate the potential protective role of MG and the mechanisms against methotrexate (MTX) induced bone damage in rats. A total of 28 Sprague-Dawley rats were divided into four groups: i) control; ii) MG, rats were treated orally with 50 mg/kg/day of MG, iii) MTX, rats were injected with 0.75 mg/kg of MTX from 8th to 12th day for 5 days and iv) MTX+MG group, rats were treated with 50 mg/kg/day of MG and injected with MTX from 8th to 12th day for 5 days. MTX pretreatment increased blood urea nitrogen and creatinine levels and aminotransferase enzyme activities, while tibia osteocalcin levels and bone mineral density (BMD) decreased (p < 0.001). MG pretreatment markedly attenuated aminotransferases activities and creatinine levels and increased tibia osteocalcin levels and femur BMD in the MTX + MG groups. MTX treatment increased levels of bone nuclear factor kappa beta ligand receptor-activator (RANKL), interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-alpha) and decreased the bone osteoprotegerin (OPG) and type1 collagen levels (p < 0.001). The effect of MG treatment on RANKL, IL-6, TNF-alpha, OPG and type1 collagen levels induced by MTX was observed actual effects (p < 0.05). Similarly, the protective effect of MG against MTX was confirmed by histological examination. In conclusion, MG pretreatment reduced the negative effects of MTX on bone damage by improving BMD and modulation of RANKL, IL-6, TNF-alpha, OPG and type1 collagen expressions in the rats.
Keywords: methotrexate; mango ginger; bone mineral density